Federal ground : governing property and violence in the first U.S. territories - Ablavsky, Gregory (New York, NY : Oxford University Press, 2021)
Federal Ground shows how the federal government gained authority in a borderland that many groups made their own claims to control. Although on paper the federal government enjoyed almost exclusive control over the territories, it actually gained authority because territorial residents wanted things from this new federal government - confirmation of rights to land, to jurisdiction, to money. Often, those residents - Native peoples, Anglo-American settlers, French villagers - were able to successfully exploit the federal government. But they became increasingly reliant on that government in the process, couching their claims in the language of federal law and turning to federal officials to claim rights.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 11, 2021).
Keywords: Public lands -- United States -- History; Land tenure -- Law and legislation -- United States -- History; Land titles -- United States -- States -- History